La práctica del turismo ecológico en el humedal abras de mantequilla en el cantón Vinces y su contribución en el desarrollo turístico sostenible de la localidad - Jorgge Bajaña, Gorky Enrique (2020)
This research paper analyzes the factors that affect the use of natural resources in the “Abras de Mantequilla Wetland”, to inform the inhabitants of the sector, all the ecological, recreational and tourist activities that can be carried out in this beautiful rural landscape, so that tourism development contributes to the improvement of the quality of life, to the sustainable management of resources. The lack of interest of the managing authorities of the destination was verified, through the absence of environmental strategies that contribute in a general way to the conservation of the Wetland. The different research methods applied are exploratory, descriptive and analytical, which allowed us to know how these natural resources can be used for their socioeconomic growth.